The Impact Of Build-To-Order Supply Chain On The Energy Efficiency And Low Carbon Footprint: Mediating Effect Of Supply Chain Responsiveness - Chowdhury, Arkyadeep (2014)
The importance of incorporating Energy Efficient and Low Carbon Footprint practices in Malaysia is a topic which cannot be neglected. The implementation of Build-To-Order Supply Chain Management is of vital importance in order to achieve the Energy Efficient and Low Carbon Footprint standards. This study was developed in order to test the impact of Build-To-Order Supply Chain on the Energy Efficiency and the Low Carbon Footprint initiatives taking Supply Chain Responsiveness as the mediating variable for this study. After careful study on the literature and previous work, the driver of Build-To-Order Supply Chain were taken to be as Production Systems, Process Modularity,